2019
DOI: 10.13057/biodiv/d201025
|View full text |Cite
|
Sign up to set email alerts
|

The phytoremediation potential of non-edible oil-producing plants for gold mine tailings

Abstract: Abstract. Andriya NN, Hamim H, Sulistijorini, Triadiati. 2019. The phytoremediation potential of non-edible oil-producing plants for gold mine tailings. Biodiversitas 20: 2949-2957. Plants can be used as phytoremediation agents to reduce environmental pollutants including heavy metal contaminants produced due to industrial activities. The objective of this study was to analyze the morphological, anatomical, and physiological responses of four non-edible oil-producing plants namely Jatropha curcas, Ricinus comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Interestingly, in this study, Pb stress had no significant effect on plant height, increased leave number as well as leaves area of Philippine-tung (R. trisperma), suggesting that this species is resistance to Pb. The adaptability of this species to Pb has also been confirmed in other experiments using soil media contained Pb, such as Hilmi et al (2018) who observed various accessions of R. trisperma grown on gold mine tailings contained Pb, and Andriya et al (2019) who compared this species with other non-edible oilproducing plants under gold mine tailings.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, in this study, Pb stress had no significant effect on plant height, increased leave number as well as leaves area of Philippine-tung (R. trisperma), suggesting that this species is resistance to Pb. The adaptability of this species to Pb has also been confirmed in other experiments using soil media contained Pb, such as Hilmi et al (2018) who observed various accessions of R. trisperma grown on gold mine tailings contained Pb, and Andriya et al (2019) who compared this species with other non-edible oilproducing plants under gold mine tailings.…”
Section: Discussionsupporting
confidence: 59%
“…Guala et al (2010), heavy metals are toxic to legumes because they can cause chlorosis, reduced plant growth, decreased productivity, and limited nutrient uptake. Andriya et al (2019) also found that root and shoot dry weight decreased significantly in the four plants used, including J. curcas and R. trisperma, after treatment with 100% tailings.…”
Section: Resultsmentioning
confidence: 74%
“…Gold mine tailings have a relatively high Pb content than non-essential heavy metals (Hilmi et al 2018). Pb levels in the tailings and soil were 63.31 ppm and 13.44 ppm, respectively (Andriya et al 2019). Therefore, these results are consistent with Hamim et al (2020a), which found that treatment of Pb up to 0.5 mM in water culture did not significantly affect the photosynthetic rate in P. conjugatum, M. micrantha, C. kyllingia, and B. mutica.…”
Section: Gas Exchange Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…Some experiment recorded that increasing the concentration of metal such as lead was directly proportional to the increase in the MDA level in the plants such as in spinach and wheat, Jatropha and Philippine Tung(Andriya et al, 2019;Hilmi et al, 2018;Lamhamdi et al, 2010). Gill and Tuteja (…”
mentioning
confidence: 99%